Inequalities in higher education access and completion in Brazil - Tristan McCowan; Julio Bertolin (United Nations Research Institute for Social Development (UNRISD), 2020)
While there are rapidly increasing enrolments worldwide, higher education systems are still characterized by continuing inequalities in access. Brazil is a case in point in this regard, with highly restricted admissions for those from low-income families, African descendants, and those with low parental level of education, despite the system tripling in size between 2000 and 2018. This study analyses trends in access and completion in higher education in Brazil in this period, assessing variation between federal and for-profit sectors, face-to-face and distance modes, and different degree courses, drawing on three national datasets (Higher Education Census, Enade and National Household Sample Survey). The data is analysed using the frame of availability (number and distribution of places), accessibility (ability of prospective students to take up opportunities) and horizontality (non-stratified system, avoiding hierarchies of prestige and quality). Brazil shows evidence of a rapid increase in availability of places since the late 1990s, as well as some improvements in accessibility on account of quota policies in federal universities and loan and grant policies for private universities. Yet there are major challenges to horizontality on account of the preponderance of disadvantaged students in lower quality for-profit institutions, in degree courses with lower value on the employment market and in distance education. Finally, implications are drawn out for higher education policy in Brazil and beyond.
Keywords: 330; Access to higher education; affirmative action; Brazil; inequalities; stratification; widening participation